Mechanisms Regulating the Dynamics of Photosynthesis Under Abiotic Stresses - Muhammad, Izhar; Shalmani, Abdullah; Ali, Muhammad; Yang, Qing-Hua; Ahmad, Husain; Li, Feng Bai (Frontiers in Plant Science, 2021)
Photosynthesis sustains plant life on earth and is indispensable for plant growth and development. Factors such as unfavorable environmental conditions, stress regulatory networks and plant biochemical processes limits the photosynthetic efficiency of plants and thereby threaten food security worldwide. Although numerous physiological approaches have been used to assess the performance of key photosynthetic components and their stress responses, though, these approaches are not extensive enough and do not favor strategic improvement of photosynthesis under abiotic stresses. The decline in photosynthetic capacity of plants due to these stresses is directly associated with reduction in yield. Therefore, a detailed information of the plant responses and better understanding of the photosynthetic machinery could help in developing new crop plants with higher yield even under stressed environments. Interestingly, cracking of signaling and metabolic pathways, identification of some key regulatory elements, characterization of potential genes and phytohormone responses to abiotic factors have advanced our knowledge related to photosynthesis, However, our understanding of dynamic modulation of photosynthesis under dramatically fluctuating natural environments remains limited. Here, we provide a detailed overview of the research conducted on photosynthesis to date, and highlight the abiotic stress factors (heat, salinity, drought, high light and heavy metal) that limit the performance of the photosynthetic machinery. Further, we reviewed the role of transcription factor genes and various enzymes involved in the process of photosynthesis under abiotic stresses. Finally, we discussed the recent progress in the field of biodegradable compounds, such as chitosan and humic acid, and the effect of melatonin (bio-stimulant) on photosynthetic activity. Based on our gathered researched data set, the logical concept of photosynthetic regulation under abiotic stresses along with improvement strategies will expand and surely accelerate the development of stress tolerance mechanisms, wider adaptability, higher survival rate and yield potential of plant species.